Sosialisasi Pembuatan KTP Digital di Universitas Balikpapan - Indrayani; Rahmat; Suherna; Joni Sasmito (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Service quality is defined as the comparison between the current available service quality and the expected service quality. According to articles 34 paragraph (3) and (4) of the 1945 Constitution, the government is responsible for providing public services in Indonesia for the legal security related to public services. Digital Identity Card services related to civil registration and population administration are one form of public service provided by the government to the public. Balikpapan University collaborates with the Department of Population and Civil Registration to conduct socialization activities for the issuance of Digital Identity Cards at Balikpapan University as a form of community service.